Understanding heavy metal contamination in the vicinity of Lake Urmia, NW Iran: Environmental and health Perspectives - Saeed Hosseinpoor; Shiva Habibi; Amir Mohammadi (Heliyon, 2024)
This study addresses the potential impact of Lake Urmia on heavy metals (HMs) concentrations in the air and soil of the northern region of Lake Urmia in North West of Iran, highlighting significant environmental and health implications. The results showed different concentration levels for Arsenic (As), Cadmium (Cd), Chromium (Cr), and Lead (Pb) in soil and settled dust particles near Lake Urmia, and their concentrations exceeded recommended thresholds for Cr and Pb in some areas. Spatial distribution analysis indicated that local factors significantly affect contamination patterns, emphasizing the need for targeted interventions.The study employed enrichment factor (EF) assessment and potential ecological risk (PER) index to identify pollution sources and evaluate associated ecological risks. The results indicated moderate to severe pollution levels in specific regions, particularly for Pb and Cd. Health risk assessments suggest that non-carcinogenic risks are generally below hazardous levels; however, concerns remain for Cr and As exposure.Future studies should focus on long-term trends, source apportionment methodologies, and health effects of heavy metal exposure to develop effective pollution management strategies. Collaborative, interdisciplinary approaches will be crucial in mitigating heavy metal pollution and protecting human and environmental health.